Permasalahan yang Dihadapi oleh Anak Panti Asuhan di Kota Padang dan Implikasinya terhadap Pelayanan Bimbingan dan Konseling - Venny Nilam Sari; Mudjiran Mudjiran; Yusri Yusri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2014)
Ideally, orphans that live in orphanage don’t have any trouble with the environment. In fact, orphans frequently coped with troubles in orphanage environment. This research is purposed to find out troubles that related to social live, learning activity, and daily needs in orphanage environment. This research is descriptive research. Sample of this research is 40 orphans whose enter junior and senior high school. Instrument in this research is questionnaire. Results of this research reveal that orphans frequently faced unbalanced communication in orphanage environment, and also they get trouble with learning activity which is studying previous lesson. Orphans also have a trouble to fulfill their daily needs in orphanage environment.